From workfare to edfare: An Africentric feminist epistemology of welfare, education, and work - Vanessa Sheared (Adult Education Research Conference, 1993)
This study offers: 1) a conceptual analysis of "marginalization," and Africentric feminism; and 2) provides a critique of African-American women's experiences with the welfare program, and the corresponding relationship of education to work.